Functional Relations among Constructs in the Same Content Domain at Different Levels of Analysis: A Typology of Composition Models - CHAN, David (Institutional Knowledge at Singapore Management University, 1998)
Composition models specify the functional relationships among phenomena or constructs at different levels of analysis (e.g., individual level, team level, organizational level) that reference essentially the same content but that are qualitatively different at different levels (M. T. Hannan, 1971, K. H. Roberts, C. L. Hulin, & D. M. Rousseau, 1978, D. M. Rousseau, 1985). Specifying adequate composition models is a critical component of good multilevel research. A typology of composition models is proposed to provide a framework for organizing, evaluating, and developing constructs and theories in multilevel research. Five basic forms of composition are described and illustrated. Implications of the typology are discussed